Relationship between Spiritual Health and Quality of Life in Post-Traumatic Stress Disorder Veterans - B. Pouraboli; S.V. Hosseini; S. Miri; B. Tirgari; M. Arab (Afarand Scholarly Publishing Institute, 2015)
Aims: Due to the stressful war happenings, the veterans are facing with physical and mental problems, which might considerably affect their quality of life. Based on the conducted studies, spirituality and spiritual health play important roles to enhance the quality of life of the veterans. The aim of this study was to investigate the correlation between spiritual health and quality of life in veterans with PTSD recorded by Martyrs and Veterans Foundation of Kerman.    Instrument and Methods: In the descriptive-correlational study, 143 veterans with PTSD recorded by Martyrs and Veterans Foundation of Kerman were selected via random sampling in 2013. Data was collected, using Spiritual Health Questionnaire and Quality of Life Questionnaire. Data was analyzed in SPSS 18 software using Independent T, One-way ANOVA, and Pearson Correlation Coefficient tests. Findings: Mean total score of the veterans' spiritual health was 87.97±12.30. 81.8% of the veterans were moderately spiritually healthy. Mean total scores of mind health and physical health of quality of life were 40.92±8.52 and 61.55±10.27, respectively. There was a significant correlation between the veterans' spiritual health and quality of life (p<0.001; r=0.43). Conclusion: There is a direct correlation between quality of life and spiritual health in veterans with PTSD recorded by Martyrs and Veterans Foundation of Kerman. In addition, the higher the spiritual health, the higher the quality of life of the veterans is.